An Efficient Privacy Preserving Search Scheme with Access Control for Cloud Data Centers. (2016) - George, V. Tresa Mary; Shamna, S.; Kizhakkethottam, Jubilant J.
Abstract: The internet and the emergence of social networks produce terabytes of data every day. In this big data scenario, the ability to outsource the data to a cloud storage facility saves the data management and storage facility cost. Some major challenges with this scheme are providing security and ensuring the privacy of the outsourced data. Although data security can be achieved through encryption, searching on encrypted data become a complex task. The proposed work suggests an efficient searching scheme for encrypted cloud data based on hierarchical clustering of documents. The hierarchical clustering method preserves the semantic relationship between the documents in the encrypted domain to speed up the search process. Consequently, the proposed system has linear computational complexity during the search phase in response to an exponential increase in the number of documents. The system also ensures data privacy by providing only limited access of the documents to the different types of users by implementing access control mechanisms resulting in more secured data storage in the cloud.